XIST and TSIX: Novel Cancer Immune Biomarkers in PD-L1-Overexpressing Breast Cancer Patients - Salama, Esraa A.; Adbeltawab, Reda E.; El Tayebi, Hend M. (Frontiers in Oncology, 2020)
Escaping antitumor immunity is a hallmark in cancer progression. Programmed cell death protein 1 (PD-1) is an immune checkpoint receptor responsible for the maintenance of immune tolerance; PD-1 ligand (PD-L1) is overexpressed in tumor cells simplifying their escape from the immune system through T cell function suppression. Notwithstanding that CA125, CEA, CA15-3, and AFP are among conventional breast-cancer diagnostic biomarkers, their lack of sensitivity and specificity resides among their major limitations. Furthermore, HER2 and IL-6—demonstrated as breast-cancer immune biomarkers—still possess limitations, for instance, technical detection problems and stability problems, which necessitates the discovery of novel, stable noninvasive cancer immune biomarkers. XIST and TSIX are two lncRNAs possessing a role in X chromosome inactivation (XCI) as well as in breast cancer. In the present study, they were investigated as stable noninvasive breast-cancer immune biomarkers. The study demonstrated that PD-L1 was overexpressed in the different molecular subtypes of breast-cancer patients as well as in MDA-MB-231 cells. Furthermore, lncRNAs XIST and TSIX were markedly increased in the tissues, lymph nodes, and different body fluids of breast-cancer patients compared to controls. In addition, XIST and TSIX were differentially expressed in subtypes of breast-cancer (BC) patients and their levels were correlated to PD-L1 expression level. In conclusion, this correlative study has shed the light on the role of both lncRNAs XIST and TSIX as potential noninvasive breast-cancer immune biomarkers reflecting the evaded immune system of the patient and overcoming the instability problem of the common breast-cancer biomarkers.